Empowerment of Elementary School Teacher in Border Area - Anrianus Anrianus; M Chiar; Sukmawati Sukmawati (STKIP Singkawang, 2018)
Empowerment of teachers is one form of effort that can be done to improve the process of education in schools. This study aims to find out how the process of teacher empowerment at Sontas 03 State Elementary School (SD Negeri 03 Sontas) Entikong Subdistrict, Sanggau Regency which formulated in several questions related to planning, implementation, supervision, and effectiveness of teacher empowerment at Sontas 03 State Elementary School in Entikong sub-district. The approach used in this research is qualitative descriptive with case study research type. Data collection using interview techniques, documentation and documentation. Data analysis using Miles and Huberman analysis model consist of four stages that are data reduction, data presentation, conclusion or verification. Checking or testing the validity of data is done by triangulation, member check, and increasing persistence. Summaries conducted to analyze the research findings such as: 1) Sontas 03 State Elementary School in Entikong sub-district has implemented a program of planning activities empowerment of teachers as well; 2) Teacher empowerment activities at Sontas 03 State Elementary School in Entikong sub-district have been implemented well; 3) Supervision of teacher empowerment at Sontas 03 State Elementary School in Entikong sub-district has been well implemented by supervisor and principal; 4) Empowerment of teachers at Sontas 03 State Elementary School in Entikong sub-district has been effective, the main activity of teacher empowerment is absolute.